Factors Impacting Job Satisfaction Levels Among Physiotherapists In Uttar Pradesh - Sharma, Vikas; Zafar, Shahiduz (Journal of Neonatal Surgery, 2025)
This research considers variables affecting job satisfaction among physiotherapists in Uttar Pradesh, with an emphasis on age, experience, workload, and patient volume. A cross-sectional survey of 302 physiotherapists compared job satisfaction differences across various demographic categories. Results show there are significant differences in job satisfaction (p < 0.001). Young physiotherapists (21-27 years: 142.1 ± 13.908) were more satisfied than mid-career professionals (42-48 years: 134.89 ± 12.663). In a similar fashion, novice physiotherapists (0-2 years: 141.25 ± 13.583) were more satisfied compared to mid-career practitioners (6-10 years: 136.00 ± 11.155). Weak but significant correlation was established between age (r = 0.370, p = 0.043) and experience (r = 0.399, p = 0.050) and job satisfaction.Mid-career discontent could be due to heavy workload and lack of career advancement. Resolution of these concerns by means of enhanced work-life balance, career progression, and pay can enhance job satisfaction. Future studies need to identify other workplace factors to enhance retention and wellness among physiotherapists.Top of Form